Morphology and habitat suitability of Rhacophorus barisani (Harvey, Pemberton & Smith, 2002) in Karo Regency, North Sumatra - Muhammad Iqbal H. Tambunan; Yusran Efendi Ritonga (Universitas Islam Negeri Sumatera Utara, 2025)
Research on Rhacophorus barisani (Harvey, Pemberton & Smith, 2002) has been limited since its formal description in 2002. Since 2017, the IUCN has classified the Barisan Tree Frog as Least Concern, and this species is endemic to the mountain forests of the Bukit Barisan Mountains in Sumatra. Published records are limited to distribution notes and photographs, with no previous reports from Karo Regency, North Sumatra. This study was conducted between September and November 2023 in the Bukit Barisan Grand Forest Park (Tahura) and Gunung Sibuatan Protected Forest. The methods used were Visual Encounter Survey-Night Stream (VES-NS) and purposive sampling. This species was described morphologically and morphometrically, and habitat suitability data were recorded based on abiotic parameters. R. barisani was found in flowing water habitats and still water pools within the forest. R. barisani has three distinct dorsal color patterns: a light brown base color with a yellowish-brown color on the back that does not reach the sides of the body; a uniform yellowish-brown base color with yellow edges and a distinct dorsal pattern and black bands on the limbs; a green base color with scattered brown or black protuberances on the back, and a snout-vent length ranging from 41.9 to 65.7 mm. The habitat suitability of this species occupies riparian and lotic areas. Critically, we confirm that this species is the first record in Karo Regency, representing a new local discovery.